Polarization fatigue in ferroelectric Pb(Zr0.52Ti0.48)O3-SrBi2Nb2O9 ceramics - Orapim Namsar (2018)
© 2015, The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht. Ferroelectric fatigue induced by cyclic electric loading of the (1-x)PZT-xSBN ceramics (0.1 ≤ x ≤ 0.3) have been investigated in comparison with pure PZT and SBN ceramics. The results showed that pure PZT ceramic possessed severe polarization fatigue after long bipolar switching pulses. This was mainly attributed to the appearance of microstructural damage at the near-electrode regions. Whereas, pure SBN ceramic exhibited no fatigue at least up to 1 × 10 < sup > 6 < /sup > switching cycles. The fatigue-free behavior of SBN ceramics was due primarily to weak domain wall pinning. PZT-SBN ceramics showed less polarization fatigue up to 1 × 10 < sup > 6 < /sup > switching cycles than pure PZT. This could be attributed to their low oxygen vacancy concentration. Therefore, this new ceramic PZT-SBN system seems to be an alternative material for replacing PZT in ferroelectric memory applications. [Figure not available: see fulltext.]